UNFOLDING THE DOUBLE SHUFFLE STRUCTURE OF $q$-MULTIPLE ZETA VALUES - CASTILLO-MEDINA, JAIME; EBRAHIMI-FARD, KURUSCH; MANCHON, DOMINIQUE (Bulletin of the Australian Mathematical Society, 2015)
We exhibit the double $q$-shuffle structure for the $q$MZVs introduced by Ohno et al. [‘Cyclic $q$-MZSV sum’, J. Number Theory132 (2012), 144–155].